Oral Anticoagulation Timing in Patients with Acute Ischemic Stroke and Atrial Fibrillation - Chang, Po-Yin; Wang, Wei-Ting; Wu, Wei-Lun; Chang, Hui-Chin; Chen, Chen-Huan; Tsai, Yi-Wen; Chiou, Shih-Hwa; Lip, Gregory Y. H.; Cheng, Hao-Min; Chiang, Chern-En (Thrombosis and Haemostasis, 2021)
Background and Purpose Oral anticoagulants (OACs) prevent stroke recurrence and vascular embolism in patients with acute ischemic stroke (AIS) and atrial fibrillation (AF). Based on empirical consensus, current guidance recommends a “1–3–6–12 days” rule to resume OACs after AIS. This study investigated the suitability of guideline-recommended timing for OAC initiation.Methods Using data of 12,307 AF patients hospitalized for AIS, for the period 2012 to 2016, in Taiwan's National Health Insurance Research Database, we constructed a sequence of cohorts of OAC users and propensity score-matched nonusers, creating one cohort on each day of OAC initiation for 30 days since admission. Composite outcome included effectiveness (cardiovascular death, ischemic stroke, myocardial infarction, transient ischemic attack, systemic embolism, and venous thromboembolism) and safety (intracranial hemorrhage, gastrointestinal bleeding, and hematuria) outcomes. Comparing with nonusers, we examined the risks in the early OAC use (within 1–3–6–12 days) or guideline-recommended delayed use. Indirect comparison between the early and delayed use was conducted using mixed treatment comparison.Results Across the AIS severity, the risks of composite or effectiveness outcome were lower in OAC users than nonusers, and the risks were similar between the early and delayed use groups. In patients with severe AIS, early OAC use was associated with an increased risk of safety outcome, with a hazard ratio (HR) of 1.67 (confidence interval [CI]: 1·30–2·13) compared with nonusers and a HR of 1.44 (CI: 0·99–2·09) compared with the delayed use.Conclusion Our study findings support an early OAC initiation in AF patients with mild-to-moderate AIS and a routine delayed use of OACs can be considered in those with severe AIS to avoid a serious bleeding event.
Keywords: atrial fibrillation; acute ischemic stroke; oral anticoagulants; timing; stroke recurrence